The round-the-clock technique for correction of gynecomastia - Mauro Tarallo (Archives of Plastic Surgery, 2019)
Background Gynecomastia is a common condition that can cause severe emotional and physical distress in both young and older men. Patients in whom symptomatic recalcitrant gynecomastia persists for a long time are potential candidates for surgery. Methods From January 2014 to January 2016, 15 patients underwent correction of gynecomastia through a single 3-mm incision at our institution. Only patients with true gynecomastia underwent surgery with this new technique. Through the small incision, sharp dissection was performed in a clockwise and counterclockwise direction describing two half-circles. Health-related quality of life and aesthetic outcomes were evaluated using a modified version of the Breast Evaluation Questionnaire (BEQ). Results The patients’ average age was 23.5 years (range, 18–28 years), and their average body mass index was 23.2 kg/m2 (range, 19.2–25.3 kg/m2). One case was unilateral and 14 cases were bilateral. The weight of glandular tissue resected from each breast ranged from 80 to 170 g. No excess skin was excised. Bleeding was minimal. The mean operating time was 25 minutes (range, 21–40 minutes). No complications were recorded. All lesions were histologically benign. The patients’ average score was 3.5 (on a 5-point Likert scale) in all domains of the BEQ for themselves and their partners. Conclusions In this study, we demonstrated the safety and reliability of a new technique that allows mastectomy through an imperceptible 3-mm incision. We obtained high patient satisfaction scores using our surgical technique, and patients reported considerable improvement in their social, physical, and psychological well-being after surgery.